Can open audit committee chairs cure the chilling effect of management's presence on auditors' information sharing during audit committee meetings? - Helikum, Lukas J.; Jamal, Karim; Tan, Hun-Tong; Xiao, Li (Accounting, Organizations and Society, 2026)
This study experimentally examines how the leadership style of the audit committee (AC) chair (controlling or open) influences the amount of discretionary information that auditors intend to share with the AC, in the context of common meeting formats (i.e., AC meetings with versus without management present, or private meetings between the auditor and AC chair). Participants are highly experienced auditors, including partners and (senior) managers, from Big 4 accounting firms. We predict and find that an open AC chair mitigates the chilling effect of management's presence on the number of discretionary issues shared with the AC. Compared to those who attend AC meetings only, auditors who engage in private meetings with the AC chair before AC meetings plan to disclose fewer discretionary issues to the AC in subsequent AC meetings, but disclose more discretionary issues in total across meetings. AC chair leadership style has no impact on their discretionary information sharing in these private meetings. These results suggest that open AC chairs can mitigate the adverse effect of management's presence on auditors' discretionary information disclosure and have implications for regulators aiming to enhance corporate governance.